Checklist of the Ichneumonidae (Insecta, Hymenoptera) of Ukraine - Varga, Oleksandr (Zootaxa, 2024)
This paper provides the first summary on the distribution of the Ukrainian Ichneumonidae based on both literature and collection resources. The checklist contains 1,840 species, of which 42 are first records from Ukraine and Apoclima rossicum Humala, 2007 is the first record from Western Palaearctic. The condition and representativeness of the national collection of Darwin wasps and prospective directions for further studies are discussed.